Use of Bipolar Radiofrequency Catheter Ablation in the Treatment of Cardiac Arrhythmias - Soucek, Filip; Starek, Zdenek (Current cardiology reviews, 2018)
BACKGROUND: Arrhythmia management is a complex process involving both pharmacological and non-pharmacological approaches. Radiofrequency ablation is the pillar of nonpharmacological arrhythmia treatment. Unipolar ablation is considered to be the gold standard in the treatment of the majority of arrhythmias; however, its efficacy is limited to specific cases. In particular, the creation of deep or transmural lesions to eliminate intramurally originating arrhythmias remains inadequate. Bipolar ablation is proposed as an alternative to overcome unipolar ablation boundaries. RESULTS: Despite promising results gained from in vitro and animal studies showing that bipolar ablation is superior in creating transmural lesions, the use of bipolar ablation in daily clinical practice is limited. Several studies have been published showing that bipolar ablation is effective in the treatment of clinical arrhythmias after failed unipolar ablation, however, there is inconsistency regarding the safety of bipolar ablation within the available research papers. According to research evidence, the most common indications for bipolar ablation use are ventricular originating rhythmic disorders in patients with structural heart disease resistant to standard radiofrequency ablation. CONCLUSION: To allow wider clinical application the efficiency and safety of bipolar ablation need to be verified in future studies.
Keywords: Catheter Ablation; safety.; Humans; lidé; radiofrequency ablation; heart disease; katetrizační ablace; Bipolar radiofrequency ablation; arrhythmias; Heart Diseases; efficacy; srdeční arytmie; Arrhythmias, Cardiac; nemoci srdce